Financial education for youth - Stoica, Dumitru (CEP USM, 2024)
“Financial Education for YOUTH” aims to analyze the impact of financial education on young people in a global economy marked by digitalization and competitiveness. The purpose of the article is to highlight the importance of developing financial skills among the youth to prepare them to successfully navigate the digitalized economic environment. It also aims to identify digital strategies that can enhance their competitiveness in the labor market and entrepreneurial development.
Keywords: digitalization; global economy; competitiveness; digital strategy